Effects of aerobic exercises in prediabetes patients: a systematic review and meta-analysis - Wang, Yifei; Li, Honglei; Yang, Dongxue; Wang, Mengzhao; Han, Yanbai; Wang, Hongli (Frontiers in Endocrinology, 2023)
Aims: To evaluate the effects of different durations of continuous aerobic exercise on prediabetic patients. Materials and methods: The research encompassed randomized controlled trials that examined how various durations of aerobic exercise training affected outcomes related to Body Mass Index (BMI), Fasting blood glucose (FBG), 2-hour plasma glucose (2hPG), and glycated hemoglobin (HbA1c) in individuals diagnosed with prediabetes. PubMed, Embase, Web of Science, and the Cochrane Library were searched as of January 7, 2023. The Cochrane Risk of Bias, version 2 (ROB 2) tool was used to assess the risk of bias. Results: A total of 10 RCTs with 815 prediabetic patients were included. The average age of the participants was 56.1 years, with a standard deviation of 5.1 years. Among the participants, 39.2% were male. The interventions consisted of aerobic dance, treadmill running, walking, and a combination of aerobic exercises. The training sessions occurred three or four times per week. In prediabetic patients, aerobic exercise demonstrated a significant reduction in BMI compared to the control group, with a weighted mean difference (WMD) of -1.44 kg/m2 (95% confidence interval [CI] -1.89, -0.98). There was a decrease in FBG levels, with WMD of -0.51 mmol/L (95% CI -0.70, -0.32). Additionally, aerobic training led to significant improvements in 2hPG levels, with a WMD of -0.76 mmol/L (95% CI -1.14, -0.38). Furthermore, prediabetic patients showed a decrease in HbA1c levels after engaging in aerobic training compared to the control group, with a WMD of -0.34% (95% CI -0.45, -0.23). Conclusion: In summary, engaging in aerobic exercise can have a significant positive impact on glycemic levels in individuals with prediabetes. It can also lead to reductions in BMI, FBG, 2hPG, HbA1c, and other relevant indicators. The extent of these improvements may vary slightly depending on the duration of the aerobic exercise intervention.